PENGARUH QUALITY WORK OF LIFE DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA RSUD KABUPATEN BULELENG - Putu Novia Wijayanti; Ni Luh Eka Ayu Permoni (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2022)
This study aims to determine the effect of work quality of life and work motivation on employee job satisfaction at Buleleng District Hospital. This study uses a quantitative approach with questionnaire data collection techniques. The number of samples in this study were 56 respondents. The analytical technique used in this study uses multiple linear regression analysis with the help of the SPSS program. The results showed that the quality of work of life and work motivation had an effect on job satisfaction in Buleleng District Hospital which was supported by the results of hypothesis testing with the T-Test test, it was found that t-count > t-table so that the hypothesis was accepted